Hospitalisation from seasonal influenza among persons with type 1 diabetes: a cohort study from the Swedish National Diabetes Register - Katarina Eeg-Olofsson; Björn Eliasson; Hanne Krage Carlsen; Lena Svensson; Magnus Gisslén; Elin Allansson Kjölhede; Oliver Martyn (BMJ Open)
Objectives The aim of this study was to investigate the risk of severe influenza resulting in hospitalisation among adults with type 1 diabetes (T1D).Design Nationwide cohort study using register data.Settings Data from the National Diabetes Register (NDR) linked to the Swedish Patient Register, Statistics Sweden and the Swedish Population Register.Participants Persons with T1D in the Swedish NDR n=35 596 and control persons from the Swedish Population Register matched on age, sex and county of residence, n=155 590.Primary and secondary outcomes Hospitalisation from seasonal influenza from October 2013 to December 2019. Season-wise incidence and HRs were analysed in the T1D group compared with controls. Secondary outcomes were associations between clinical variables and hospitalisation due to seasonal influenza for persons with T1D.Results There were 347 (1.0%) influenza admissions in persons with T1D and 332 (0.2%) in the control group. The overall incidence rate was 16.9/10 000 person-years in the T1D group and 3.6/10 000 person-years for the control group. Persons with T1D had an unadjusted HR 4.7 (95% CI 4.0 to 5.5) for risk of hospitalisation from influenza during the study period and HR 3.4 (95% CI 2.9 to 4.0) when adjusted for age, sex, socioeconomic factors and chronic medical conditions at baseline. Within the T1D cohort, individuals hospitalised due to influenza were older, were more often smokers, had lower glomerular filtration rate and more often had a previous history of ischaemic heart disease and stroke.Conclusions To our knowledge, this is the first large study to highlight that persons with T1D have a threefold higher risk of hospitalisation due to seasonal influenza compared with matched controls from the general population. It is important for healthcare professionals to acknowledge this excess risk, particularly in older persons with T1D, who have cardiovascular risk factors and reduced kidney function.